A Study on Financial Management among Generation Z in Malang City - Turosida, Trianita Diana; Andayani, Endang Sri; Maharani, Satia Nur (Dinasti Publisher, 2026)
This research analyzes the effect of financial literacy, hedonic lifestyle, and fear of missing out (FOMO) on the financial management behavior of Generation Z in Malang City by involving locus of control as an intervening variable. The study applied a quantitative explanatory design using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with 385 respondents aged 18–27 years. The findings reveal that financial literacy does not significantly influence financial management behavior or locus of control. In contrast, hedonic lifestyle and FOMO demonstrate a significant relationship with locus of control, although FOMO does not directly affect financial management behavior. The results further indicate that locus of control positively contributes to financial management behavior and acts as a mediating variable in the relationship between hedonic lifestyle, FOMO, and financial management behavior. This study concludes that financial management behavior among Generation Z in the digital era is shaped not only by financial understanding, but also by psychological and social influences.